PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT ELA JAYA BERKAH PAMULANG TANGERANG SELATAN - Fauziah, Nurul; Komarudin Komarudin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to analyze the Influence of Leadership Style and Work Environment on Employee Performance at PT Ela Jaya Berkah Pamulang Tangerang Selatan. The research method used in this study is quantitative. The population and sample in this study were 54, using saturated sampling techniques and collection using questionnaires, data analysis techniques using linear regression analysis and hypothesis testing. The results of this study indicate: Partially Leadership Style (X1) Influences Employee Performance with a simple linear regression equation Y = 13.490 + 0.917 (X1), the correlation value rx1y 0.832, leadership style has a contribution of influence of 69.2% on performance and the remaining 30.8% is influenced by other factors, the hypothesis test shows a calculated t value of 10.805> t table 2.007 or a Sig value of 0.000 <0.05, Partially Work Environment (X2) Influences Employee Performance (Y) with a simple linear regression equation Y = a + bx is Y = 9.967 + 0.976 (X2), the correlation value rx2y 0.830, the work environment has a contribution of influence of 68.8% on performance and the remaining 31.2% is influenced by other factors, the hypothesis test shows a calculated t value of 10.719> t table 2.007 or Sig value 0.000 < 0.05. Simultaneously Leadership Style (X1) and Work Environment (X2) Influence Employee Performance (Y) with multiple linear regression equation Y = 9.198 + 0.500 (X1) + 0.516 (X2), correlation value rx1.2y 0.861, leadership style and work environment simultaneously have an influence contribution of 74.1% on performance and the remaining 25.9% is influenced by other factors, simultaneous hypothesis test shows F count value 73.048> F table 3.179 or Sig value 0.000 < 0.05 Keywords: Leadership Style, Work Environment, and Performance